2015
DOI: 10.1039/c5nr02334c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of SnO2–SnO nanocomposites with p–n heterojunctions for the low-temperature sensing of NO2 gas

Abstract: In this report, the fabrication of a novel SnO2-SnO nanostructure with p-n heterojunctions has been achieved through a facile one-pot and low-cost hydrothermal process. The structure and properties of the nanocomposite were analyzed with X-ray techniques and electron microscopy. HRTEM characterization showed that the p-n heterojunctions were formed with small n-type SnO2 nanocrystals dispersed on the surface of large p-type SnO crystals. Compared to the single SnO2-based material, a gas sensor fabricated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(69 citation statements)
references
References 57 publications
1
65
0
Order By: Relevance
“…The direct band gap is determined using this equation when the straight portion of the (αhν) 2 against hν plot is extrapolated to intersect the energy axis at α = 0. Figure 5 shows the plots of (αhν) 2 versus photon energy hν for FTO nanoparticles with [38,39]. The band gap energies of the SnO 2 materials show a decrease with the increase of doping concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The direct band gap is determined using this equation when the straight portion of the (αhν) 2 against hν plot is extrapolated to intersect the energy axis at α = 0. Figure 5 shows the plots of (αhν) 2 versus photon energy hν for FTO nanoparticles with [38,39]. The band gap energies of the SnO 2 materials show a decrease with the increase of doping concentration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The grain size of the crystallize SnO 2 is calculated to be 10 nm, according to the Scherrer formula. The formation mechanism of SnO 2 can be attributed to the following sections . First, the urea is hydrolyzed to ammonia and carbon dioxide, and then NH4+ and CO32 are produced from NH 3 and CO 2 , respectively (Equation ).…”
Section: Resultsmentioning
confidence: 99%
“…The formation mechanism of SnO 2 can be attributed to the following sections. [23][24][25] First, the urea is hydrolyzed to ammonia and carbon dioxide, and then NH þ 4 and CO 2À 3 are produced from NH 3 5). The beginning of the hydrothermal reaction speeds up the hydrolyzation of urea, and the solution changes into alkaline because of the excessive urea.…”
Section: Photocatalytic H 2 Evolutionmentioning
confidence: 99%
“…During the synthesis procedure of the precursors, 25 mL of 0. 4 6 , or Ni(OH) 2 was placed in a mixture of 10 mL deionized water and 3 mL 1 mg mL À1 HAuCl 4 $4H 2 O solution. For the purpose of achieving good mixing uniformity, the solutions were stirred at room temperature for 4 hours and preserved in three Teon-lined stainless-steel autoclaves at 120 C for 1 hour.…”
Section: Synthesis Of the Hierarchically Porous Metal Oxidesmentioning
confidence: 99%
“…[1][2][3][4] Among them, metal oxide gas sensors possess obvious advantages such as rapid responsiveness, low cost, high sensitivity and long service life, and account for 60% of gas sensors on the market. [5][6][7][8] Previous studies have shown that metal oxide gas sensors have better sensing performance in the detection of volatile organic compounds (VOC).…”
Section: Introductionmentioning
confidence: 99%